Follicular Dowling-Degos Disease with Hidradenitis Suppurativa: A Case Report and Review of the Literature - Ya Nin Nokdhes (2022)
Dowling-Degos disease (DDD) is an autosomal dominant disorder with variable phenotypic expression. Classically, DDD is characterized by progressive reticulate hyperpigmentation on flexures with perioral pitted scars and comedone-like hyperkeratotic papules. Follicular DDD is a rare variant which was introduced by Singh et al. [Indian J Dermatol Venereol Leprol. 2013 Nov-Dec;79(6):802-4]. Follicular DDD differs from other variants because of its notable comedone-like hyperkeratotic hyperpigmented papules and a distinct histopathology which demonstrates pigmented filiform and branching rete pegs originating at the follicular infundibulum with many epidermal horn cysts while the interfollicular epidermis is essentially normal. Hereby, we present a case of follicular DDD with hidradenitis suppurativa (HS). A 37-year-old Thai man presented with slowly progressive hyperpigmented comedone-like papules on the face, neck, axillae, upper trunk, and buttocks with perioral pitted scars. Punch biopsy from a comedonal lesion on his back was consistent with follicular DDD. He also had recurrent painful nodules and abscess on the back, groin, and buttock which matched the clinical criteria for the diagnosis of HS. To date, a paucity of concurrent DDD with HS has been reported. Recent genetic studies speculate a shared pathophysiologic mechanism of DDD and HS.